(3GdQSGdI GdSjajI aj GdCOhjI GdedhcjIs - (3gHI Gddg Hf RjO Hf MSf Hf GaQGFje Hf jYbhH Hf LejY GdGSQGFjdj, GdeJWHH GdeUQj,J (B594 (3g` s
(3ChdgG (B:s
(3bGd Cf GdSjO GdCLd Gdedc XgjQ GdOjf TgGH CejQ GdeDefjf de cGf CMb ef LdjJ CHcGQ GdacQ hChdi ef CgOjJ Edjg KeGQ GdHMK hcGf eeG GSJNQLg HWQjb GdbjGS COhjI edhcjI ddbhdfL dPjOI GdWYe s
(3BNQgG (B:s
(3gPg GdGOhjI COGe Gddg JCjO Gdehdi CjgG GdeSJYed ai hbJ GdMGLI Edjg hGdMeOddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3gPg GdfSNI bhHdJ hUMMJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B72s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs